Association between routine biomarkers and atrial fibrillation in patients undergoing implantation of a dual‐chamber pacemaker. Issue 1 (17th December 2020) - Kyrlas, Konstantinos; Liu, Tong; Bazoukis, George; Plakoutsi, Sofia; Liberopoulos, Evangelos; Milionis, Haralampos; Korantzopoulos, Panagiotis
Abstract: Background: Elderly patients having a permanent pacemaker frequently have atrial remodeling. We examined the association between routine biomarkers and atrial fibrillation (AF) in patients receiving a dual‐chamber pacemaker for sinus node disease (SND) or second‐/third‐degree atrioventricular block. Methods: We recorded clinical, laboratory, and electrocardiographic parameters as well as pacemaker lead parameters at implantation. The final analysis included 217 patients with SND and 393 patients with atrioventricular block. Notably, 102/217 (47%) of the SND patients (median age: 77 years, 54% men) and 54/393 (14%) of the atrioventricular block patients (median age: 79 years, 54% men) had AF history (paroxysmal or persistent). Results: Multivariable analysis showed that red blood cell distribution width (RDW) (OR: 1.17; 95% CI: 1.05‐1.36; P = .05) and serum γ‐glutamyl transferase (γGT) levels (OR: 1.15; 95% CI: 1.03‐1.28; P = .04) were independently associated with AF history in patients with SND. In ROC curve analysis, the area under the curve (AUC) was 0.648; P < .01 for RDW, and 0.753; P < .01 for γGT. A RDW cut‐off point of 14 was associated with AF with a sensitivity of 67% and a specificity of 68%, while a γGT cut‐off point of 21 was associated with AF with a sensitivity of 80% and a specificity of 65%. In patients with second‐/third‐degree atrioventricular block, there were no significant independent correlations between AF and the parameters studied. Conclusions: In elderly patients with SND, RDW and γGT have an independent association with AF history. Our study failed to show any corresponding associations in patients with advanced disorders of atrioventricular conduction.